Capital Investments and Trade Balances Within the British Empire - Boggs, Theodore H. (Quarterly Journal of Economics, 1915)
Introductory. Effects of international lending and borrowing on imports and exports, 769. — I. British India. The debit and credit items, 770. — Tabular statements, 772. — Foreign capital investments and interest charges, 775. — Obvious gain from productive investments, 779. — II. Canada's heavy borrowings, 780. — Halt in 1914, 783. — Exports and imports, 785. — “Invisible” items, 786. — Approximate balance sheet, 790. — Imports from United States, 791.